Fluorescence enhanced substrate for targeted detection of norfloxacin and preparation method of fluorescence enhanced substrate
By applying molecular imprinting technology on fluorescence enhancement substrates, a specific molecular imprinting film is formed, which solves the problems of low detection sensitivity of norfloxacin and expensive equipment in the prior art, and achieves high sensitivity, wide linear range and low cost detection effects.
Patent Information
- Application Number
- CN202411958150.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art has problems such as low sensitivity, low detection limit, high environmental impact and expensive equipment when detecting norfloxacin, making it difficult to achieve high sensitivity, wide linear range and trace detection.
A fluorescence enhancement substrate is designed, including substrate, precious metal particles and fluorescence detection layer. A specific molecular imprint film is formed on the fluorescence detection layer through molecular imprinting technology, and the targeted detection of norfloxacin is achieved by using changes in fluorescence signals.
It realizes high sensitivity detection for norfloxacin, with a detection limit of 0.010~0.050μmol/L, with high stability, high selectivity and low cost, and is suitable for fast and accurate environmental monitoring.
Smart Images

Figure CN119827464A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectric sensor devices, and in particular relates to a fluorescence enhancement substrate for targeted detection of norfloxacin and a preparation method thereof. Background Art
[0002] Norfloxacin (NOR) is a third-generation quinolone drug, widely used in medicine, a type of antibiotic with broad-spectrum antibacterial effects. However, after quinolone drugs are taken in and metabolized by organisms, most of the active ingredients are still not decomposed, and due to the poor treatment effect of antibiotics in current traditional sewage treatment plants, norfloxacin has been detected in water environments such as surface water, seawater, drinking water, and wastewater, and eventually enters the environmental system; and due to the abuse of norfloxacin, the cumulative environmental effects caused have an impact on the ecological environment that cannot be ignored, and it poses a long-term and potential threat to animals, plants, and humans. Therefore, it is urgent to develop an effective, sensitive and rapid method for detecting norfloxacin; such as ultraviolet visible spectrophotometer, Raman spectroscopy, liquid chromatography-tandem mass spectrometry (LC-MS / MS), chemiluminescence immunoassay, enzyme immunoassay (EIA) and other methods for quantitatively determining norfloxacin; however, the above detection methods have certain disadvantages, such as ultraviolet visible spectrophotometer detection means is relatively simple, but it is easily disturbed by the external environment, the sensitivity is too low, and the detection limit is low; the chemiluminescence analysis method is greatly affected by the polarity, pH, concentration and other factors of the environmental solvent, and the repeatability is relatively poor; the instrument used in Raman spectroscopy is expensive, and is greatly affected by the environment and has poor uniformity; liquid chromatography-tandem mass spectrometry (LC-MS / MS) and enzyme immunoassay (EIA) require expensive equipment; therefore, it is now urgent to develop a sensor that can detect NOR conveniently and quickly, with high sensitivity, wide linear range and trace amounts.
[0003] Molecular imprinting technology is similar to antigen-antibody specific recognition technology. It defines the target molecule as the template molecule. The template molecule and the functional monomer rely on interaction forces, such as covalent bonds, non-covalent bonds, hydrogen bonds, and van der Waals forces to form a prepolymer; then, under the copolymerization of the crosslinker and the initiator, a highly cross-linked prepolymer is formed around the prepolymer. Then, by destroying the interaction between the template molecule and the functional monomer, the template molecule is eluted from the polymer, thereby forming a three-dimensional imprinted structure on the polymer that matches the shape, size, and action site of the template molecule. This imprinted structure is similar to a "lock" structure, and the functional monomer is a molecular key, so that the template molecule can be specifically recognized. Molecular imprinted polymers (MIPs) have the advantages of simple preparation, simple detection, good specificity, good stability, good sensitivity, and low price, so they are widely used in sensing detection. However, molecular imprinted polymers are just like a specific recognition element that can specifically recognize NOR. This specific recognition needs to be converted into a measurable signal to achieve qualitative and quantitative detection, such as fluorescence, Raman, light absorption, electrochemistry and other technologies to achieve specific detection. However, fluorescence technology stands out among many detection technologies due to its advantages such as simple detection means, relatively cheap detection instruments, good fluorescence stability, and various types of fluorescence detection. Fluorescence detection technology is widely used in sensing detection directions such as biochemistry, analytical chemistry, biotechnology, food, and agricultural technology, and has high sensitivity and a wide linear detection range. The specific detection of molecular imprinting is expressed in the form of light by using the change of fluorescence signal, thereby realizing the sensing detection of target molecules; and by designing fluorescence quenching or enhancement, fluorescence detection is combined with molecular imprinting technology to prepare highly stable, highly sensitive, and highly selective molecular imprinting fluorescence sensors, which have become a research hotspot in the field of sensing. Summary of the invention
[0004] The present invention provides a fluorescence enhancement substrate for targeted detection of norfloxacin, comprising: a substrate; noble metal particles located on the surface of the substrate; and a fluorescence detection layer located on the surface of the noble metal particles; wherein the substrate and the noble metal particles have a fluorescence enhancement effect.
[0005] In one embodiment of the present invention, the substrate is one or more of single crystal silicon, polycrystalline silicon, quartz, glass, fluorine-doped tin dioxide conductive glass, indium tin oxide conductive glass, carbon cloth, paper, cellulose film, stainless steel, metal nickel, metal copper, metal titanium, titanium oxide, metal aluminum, aluminum oxide, indium phosphide, silicon carbide, silicon nitride, diamond, sapphire, gallium arsenide, polydimethylsiloxane, polyethylene terephthalate, polymethyl methacrylate, polyethylene, and polyvinylidene fluoride.
[0006] In one embodiment of the present invention, the substrate surface needs to be constructed into an anti-reflection structure, and the anti-reflection structure is one or more of a pyramid, column, rod, tube, nanowire, inverted pyramid, nanosheet, bowl, and porous shape.
[0007] In one embodiment of the present invention, the precious metal particles are one or more of silver, gold, copper, platinum and their alloys, the micro-nano morphology of the precious metal particles has one of bionic dendrites, bionic flowers, and bionic sea urchins, and the assembly technology of the precious metal particles includes one or more of chemical deposition technology, electrodeposition technology, electrical displacement reaction technology, and photoreduction technology.
[0008] In one embodiment of the present invention, the fluorescence detection layer includes: fluorescent quantum dots; a fluorescence quenching barrier membrane located on the surface of the fluorescent quantum dots; and a molecular imprinting membrane located on the surface of the fluorescence quenching barrier membrane.
[0009] In one embodiment of the present invention, the types of fluorescent quantum dots include one or more of ZnO quantum dots, MgO quantum dots, CuO quantum dots, g-C3N4 quantum dots, CdS quantum dots, SnO2 quantum dots, MoS2 quantum dots, zinc sulfide quantum dots, zinc selenide quantum dots, cadmium selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, graphene quantum dots, and carbon quantum dots.
[0010] In one embodiment of the present invention, the material of the fluorescence quenching barrier film includes one or more of alumina, SiO2, glass, zirconium oxide, hydroxyapatite, aluminosilicate, and a polymer containing a hydrophilic group.
[0011] In one embodiment of the present invention, norfloxacin is used as a template molecule, and an organic substance containing both an amino group and a hydrolyzable group is used as a functional monomer for hydrolysis, and then norfloxacin is eluted to obtain a molecular imprinting membrane in a fluorescence detection layer. The molecular imprinting membrane contains a cavity complementary to the spatial structure of the norfloxacin molecule. When the prepared fluorescent substrate detects NOR, the molecular imprinting membrane on the substrate can sensitively identify NOR, thereby effectively quenching the fluorescence of the original substrate, thereby achieving targeted detection of NOR.
[0012] Beneficial effects of the present invention:
[0013] The detection limit of the substrate prepared by the invention for norfloxacin is 0.010-0.050 μmol / L. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The present invention provides a preparation process for the fluorescence enhancement substrate for the targeted detection of norfloxacin in Example 1 of the present invention. DETAILED DESCRIPTION
[0015] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0016] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0017] Unless otherwise specified, the raw materials used in the examples were purchased commercially.
[0018] Example 1
[0019] a. Preparation of silicon cone substrate:
[0020] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 8 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 40 minutes to obtain a silicon cone (Si-p) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;
[0021] b. Dendritic silver particle assembly:
[0022] Si-p was placed in a mixed solution of 0.01 mol / L silver nitrate and 2.0 mol / L hydrofluoric acid for 11 min to deposit dendritic silver particles (Ag ND), thereby obtaining Ag ND / Si-p;
[0023] c. Preparation of ZnO quantum dots coated with SiO2 barrier film:
[0024] 20 mL of 0.4 mol / L LiOH·H2O was added to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, and the mixture was stirred at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution. Then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to settle for 2 h. Subsequently, the mixture was centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol. Finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of the ZnO quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@ZnO.
[0025] d. Molecularly imprinted membrane modified SiO2@ZnO:
[0026] Add 150 μL 3-aminopropyltriethoxysilane (APTES) and 0.0064 g NOR to the SiO2@ZnO solution obtained in step c, stir at room temperature for 24 h, centrifuge the obtained mixture at 8000 rpm for 5 min, and discard the supernatant; finally, wash the precipitate with methanol solvent to remove NOR, and form a molecular imprinted film (MIP) on the surface of SiO2@ZnO, that is, obtain MIP@SiO2@ZnO;
[0027] e.MIP@SiO2@ZnO modification of Ag ND / Si-p:
[0028] MIP@SiO2@ZnO was dropped onto the surface of Ag ND / Si-p to obtain a fluorescence enhanced substrate (MIP@SiO2@ZnO / Ag ND / Si-p) for targeted detection of norfloxacin, and its detection limit for NOR was 0.015 μmol / L.
[0029] Figure 1 The preparation process of the fluorescence-enhanced substrate for targeted detection of norfloxacin is described.
[0030] Comparative Example 1:
[0031] a. Preparation of silicon cone substrate:
[0032] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 8 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 40 minutes to obtain a silicon cone (Si-p) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;
[0033] b. Dendritic silver particle assembly:
[0034] Si-p was placed in a mixed solution of 0.01 mol / L silver nitrate and 2.0 mol / L hydrofluoric acid for 11 min to deposit dendritic silver particles (Ag ND), thereby obtaining Ag ND / Si-p.
[0035] c. Preparation of ZnO quantum dots coated with SiO2 barrier film:
[0036] 20 mL of 0.4 mol / L LiOH·H2O was added to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, and the mixture was stirred at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution. Then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to settle for 2 h. Subsequently, the mixture was centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol. Finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of the ZnO quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@ZnO.
[0037] d. Non-molecular imprinting membrane modified SiO2@ZnO:
[0038] Add 150 μL of APTES to the SiO2@ZnO solution obtained in step c, stir at room temperature for 24 h, centrifuge the obtained mixture at 8000 rpm for 5 min, discard the supernatant, dissolve the precipitate with methanol, and form a non-molecular imprinted film (NIP) on the surface of SiO2@ZnO to obtain NIP@SiO2@ZnO;
[0039] e.NIP@SiO2@ZnO modification of Ag ND / Si-p:
[0040] NIP@SiO2@ZnO was dropped onto the surface of Ag ND / Si-p, from NIP@SiO2@ZnO / Ag ND / Si-p), which had no targeted recognition ability for NOR.
[0041] Example 2
[0042] a. Preparation of silicon cone substrate:
[0043] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 8 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 40 minutes to obtain a silicon cone (Si-p) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;
[0044] b. Dendritic silver particle assembly:
[0045] Si-p was placed in a mixed solution of 0.01 mol / L silver nitrate and 2.0 mol / L hydrofluoric acid for 11 min to deposit dendritic silver particles (Ag ND), thereby obtaining Ag ND / Si-p;
[0046] c. Preparation of MoS2 quantum dots coated with SiO2 barrier film:
[0047] 0.08 g / mL Na2MoO4.2H2O and 0.1 g / mL cysteamine hydrochloride were mixed evenly in a volume ratio of 1:2, and the pH was adjusted to 6 with 0.15 mol / L HCl solution; then, the mixture was placed in a reactor at 200°C for 36 h, and the upper light yellow MoS2 quantum dot clear solution was taken for use; subsequently, 60 mL of MoS2 quantum dot solution was added to 120 mL of n-hexane, and a white granular precipitate appeared, which was allowed to stand for 2 h; finally, the mixture was centrifuged for 10 min (2000 r / min), the upper clear solution was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent MoS2 sol; finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of MoS2 quantum dots to form a SiO2 barrier film, thereby obtaining SiO 2 @MoS2;
[0048] d. Molecularly imprinted membrane modified SiO2@MoS2:
[0049] Add 150 μL 3-aminopropyltriethoxysilane (APTES) and 0.0064 g NOR to the SiO2@MoS2 solution obtained in step c, stir at room temperature for 24 h, centrifuge the obtained mixture at 8000 rpm for 5 min, and discard the supernatant; finally, wash the precipitate with methanol solvent to remove NOR, and form a molecular imprinting film (MIP) on the surface of SiO2@MoS2, that is, obtain MIP@SiO2@MoS2;
[0050] e.MIP@SiO2@MoS2 modification of Ag ND / Si-p:
[0051] MIP@SiO2@MoS2 was dropped onto the surface of Ag ND / Si-p to obtain a fluorescence enhanced substrate (MIP@SiO2@MoS2 / Ag ND / Si-p) for targeted detection of norfloxacin, and its detection limit for NOR was 0.033 μmol / L.
[0052] Example 3
[0053] a. Preparation of silicon cone substrate:
[0054] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 8 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 40 minutes to obtain a silicon cone (Si-p) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;
[0055] b. Flower-shaped gold particle assembly:
[0056] An equal volume of 0.06 mol / L hexadecyltrimethylammonium chloride and 0.5 mmol / L tetrachloroauric acid was mixed evenly, and a 2% volume of 0.08 mol / L ascorbic acid solution was added dropwise. After stirring for 20 seconds, Si-p was placed in the mixed solution and allowed to stand at room temperature for 5 hours to deposit flower-like gold nanoparticles (Au ND), thereby obtaining Au ND / Si-p;
[0057] c. Preparation of ZnO quantum dots coated with SiO2 barrier film:
[0058] 20 mL of 0.4 mol / L LiOH·H2O was added to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, and the mixture was stirred at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution. Then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to settle for 2 h. Subsequently, the mixture was centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol. Finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of the ZnO quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@ZnO.
[0059] d. Molecularly imprinted membrane modified SiO2@ZnO:
[0060] 150 μL 3-aminopropyltriethoxysilane (APTES) and 0.0064 g NOR were added to the SiO2@ZnO solution obtained in step c, and stirred at room temperature for 24 h. The obtained mixture was centrifuged at 8000 rpm for 5 min and the supernatant was discarded. Finally, the precipitate was washed with methanol solvent to remove NOR, and the SiO2@ZnO solution was stirred for 24 h at room temperature. 2 @ZnO surface to form a molecular imprinted film (MIP), that is, MIP@SiO2@ZnO;
[0061] e. MIP@SiO2@ZnO modification of Au ND / Si-p:
[0062] MIP@SiO2@ZnO was dropped onto the surface of Au ND / Si-p to obtain a fluorescence enhanced substrate (MIP@SiO2@ZnO / Au ND / Si-p) for targeted detection of norfloxacin, and its detection limit for NOR was 0.012 μmol / L.
[0063] Example 4
[0064] a. Preparation of PDMS (polydimethylsiloxane) substrate:
[0065] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 8 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 40 minutes to obtain a silicon cone (Si-p) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;
[0066] Take 1.5g of PDMS prepolymer and 0.15g of curing agent (Sylgard TM 184silicone elastomercuring agent) and stirred for 15 minutes; then, cast it on the Si-p surface and heated it in an oven at 80°C for 90 minutes to completely cure the PDMS prepolymer, and peeled off from the Si-p surface to obtain a PDMS substrate; finally, treat the PDMS substrate with O2 plasma for 10 seconds to make its surface hydrophilic;
[0067] b. Assembly of flower-like gold particles:
[0068] Equal volumes of 0.06 mol / L hexadecyltrimethylammonium chloride and 0.5 mmol / L tetrachloroauric acid were mixed evenly, and 2% of the above volume of 0.08 mol / L ascorbic acid solution was added dropwise; after stirring for 20 seconds, a PDMS substrate was placed in the above mixed solution and allowed to stand at room temperature for 5 hours to deposit flower-like gold nanoparticles (Au ND) on its surface, thereby obtaining Au ND / PDMS;
[0069] c. Preparation of CdS quantum dots coated with SiO2 barrier film:
[0070] 1mmol of anhydrous CdCl2 and 1.7mmol of mercaptopropionic acid (MPA) were added to 20mL of water, stirred evenly and fully dissolved to obtain a colorless, clear and transparent solution; then, a 30% aqueous NaOH solution was added dropwise to the solution until the pH of the solution was >10; then, the solution was placed in a 50mL three-necked flask, and the upper gas was converted to argon using a double-row tube; then, a newly prepared aqueous Na2S solution containing 0.1mmol was quickly injected into the previously prepared Cd precursor solution while stirring; after that, the reaction solution was stirred and heated Keep the temperature at 100°C for 30 minutes to allow the quantum dots to grow; after taking out and cooling the reaction solution, add about 0.6 times the volume of acetone to it to turn the CdS quantum dots into a precipitate, and centrifuge at 8000rpm for 1 minute to separate the CdS quantum dots, remove the upper clear liquid, and add 20mL of anhydrous ethanol to dissolve the precipitate to obtain a clear and transparent CdS sol; finally, add 300μL of tetraethyl orthosilicate (TEOS) and 100μL of ammonia water to hydrolyze TEOS on the surface of the CdS quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@CdS;
[0071] d. Molecularly imprinted membrane modified SiO2@CdS:
[0072] 50 mg NOR and 500 μL acrylic acid were added to 15 mL methanol solution and stirred for 30 min. Then, 100 mg SiO2@CdS and 100 μL ethylene glycol dimethacrylate were added and ultrasonically dispersed for 30 min. Then, 20 mg azobisisobutyronitrile (AIBN) was added and polymerization was initiated under 360 nm ultraviolet light. Subsequently, the product was collected by centrifugation and washed with methanol. Finally, the obtained polymer was repeatedly eluted with a mixed solution of hydrochloric acid and methanol (1:9, v:v) to remove NOR molecules, forming a molecular imprinted film (MIP) on the surface of SiO2@CdS, i.e., MIP@SiO2@CdS was obtained.
[0073] e. MIP@SiO2@CdS modification of Au ND / PDMS:
[0074] MIP@SiO2@CdS was dropped onto the surface of Au ND / PDMS to obtain a fluorescence enhanced substrate (MIP@SiO2@CdS / Au ND / PDMS) for targeted detection of norfloxacin, and its detection limit for NOR was 0.01 μmol / L.
[0075] Example 5
[0076] a. Preparation of silicon cone substrate:
[0077] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 8 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 40 minutes to obtain a silicon cone (Si-p) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;
[0078] b. Dendritic silver particle assembly:
[0079] Si-p was placed in a mixed solution of 0.01 mol / L silver nitrate and 2.0 mol / L hydrofluoric acid for 11 min to deposit dendritic silver particles (Ag ND), thereby obtaining Ag ND / Si-p;
[0080] c. Preparation of CdS quantum dots coated with SiO2 barrier film:
[0081] 1mmol of anhydrous CdCl2 and 1.7mmol of mercaptopropionic acid (MPA) were added to 20mL of water, stirred evenly and fully dissolved to obtain a colorless, clear and transparent solution; then, a 30% aqueous NaOH solution was added dropwise to the solution until the pH of the solution was >10; then, the solution was placed in a 50mL three-necked flask, and the upper gas was converted to argon using a double-row tube; then, a newly prepared aqueous Na2S solution containing 0.1mmol was quickly injected into the previously prepared Cd precursor solution while stirring; after that, the reaction solution was stirred and heated Keep the temperature at 100°C for 30 minutes to allow the quantum dots to grow; after taking out and cooling the reaction solution, add about 0.6 times the volume of acetone to it to turn the CdS quantum dots into a precipitate, and centrifuge at 8000rpm for 1 minute to separate the CdS quantum dots, remove the upper clear liquid, and add 20mL of anhydrous ethanol to dissolve the precipitate to obtain a clear and transparent CdS sol; finally, add 300μL of tetraethyl orthosilicate (TEOS) and 100μL of ammonia water to hydrolyze TEOS on the surface of the CdS quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@CdS;
[0082] d. Molecularly imprinted membrane modified SiO2@CdS:
[0083] Add 150 μL 3-aminopropyltriethoxysilane (APTES) and 0.0064 g NOR to the SiO2@CdS solution obtained in step c, stir at room temperature for 24 h, centrifuge the obtained mixture at 8000 rpm for 5 min, and discard the supernatant; finally, wash the precipitate with methanol solvent to remove NOR, and form a molecular imprinted film (MIP) on the surface of SiO2@CdS, so as to obtain MIP@SiO2@CdS;
[0084] e. MIP@SiO2@CdS modification of Ag ND / Si-p:
[0085] MIP@SiO2@CdS was dropped onto the surface of Ag ND / Si-p to obtain a fluorescence enhanced substrate (MIP@SiO2@CdS / Ag ND / Si-p) for targeted detection of norfloxacin, and its detection limit for NOR was 0.027 μmol / L.
[0086] Example 6
[0087] a. Preparation of Ti / TiO2 substrate:
[0088] A grade 2 titanium sheet with a thickness of 0.1 mm was sliced into 2 cm × 1 cm samples; then ultrasonically cleaned in ethanol and water for 10 min respectively; after cleaning, an oxidation treatment of 30 V was applied for 10 min with graphite as the cathode, and the titanium sheet was electrochemically anodized using an ethylene glycol-based electrolyte with ammonium fluoride (1.2 wt%, 8.18 mM) and water (2 wt%) added; finally, the sample was heat treated at 400 ° C for 3 h to obtain a Ti / TiO2 substrate;
[0089] b. Dendritic silver particle assembly:
[0090] In an ethylene glycol-based electrolytic solution containing 2 mM silver nitrate (AgNO3), with a graphite plate as an anode and Ti / TiO2 as a cathode, dendritic silver particles (Ag ND) were deposited on the surface of Ti / TiO2 at an applied potential of 5 V for 30 s to obtain Ag ND / Ti / TiO2;
[0091] c. Preparation of MoS2 quantum dots coated with SiO2 barrier film:
[0092] 0.08 g / mL Na2MoO4.2H2O and 0.1 g / mL cysteamine hydrochloride were mixed evenly in a volume ratio of 1:2, and the pH was adjusted to 6 with 0.15 mol / L HCl solution; then, the mixture was placed in a reactor at 200°C for 36 h, and the upper light yellow MoS2 quantum dot clear solution was taken for use; subsequently, 60 mL of MoS2 quantum dot solution was added to 120 mL of n-hexane, and a white granular precipitate appeared, which was allowed to stand for 2 h; finally, the mixture was centrifuged for 10 min (2000 r / min), the upper clear solution was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent MoS2 sol; finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of MoS2 quantum dots to form a SiO2 barrier film, thereby obtaining SiO 2 @MoS2;
[0093] d. Molecularly imprinted membrane modified SiO2@MoS2:
[0094] Add 150 μL 3-aminopropyltriethoxysilane (APTES) and 0.0064 g NOR to the SiO2@MoS2 solution obtained in step c, stir at room temperature for 24 h, centrifuge the obtained mixture at 8000 rpm for 5 min, and discard the supernatant; finally, wash the precipitate with methanol solvent to remove NOR, and form a molecular imprinting film (MIP) on the surface of SiO2@MoS2, that is, obtain MIP@SiO2@MoS2;
[0095] e.MIP@SiO2@MoS2 modification of Ag ND / Ti / TiO2:
[0096] MIP@SiO2@MoS2 was dropped onto the surface of Ag ND / Ti / TiO2 to obtain a fluorescence enhanced substrate for targeted detection of norfloxacin (MIP@SiO2@MoS2 / Ag ND / Ti / TiO2), with a detection limit of 0.031 μmol / L for NOR.
[0097] Example 7
[0098] a. Preparation of Ti / TiO2 substrate:
[0099] A grade 2 titanium sheet with a thickness of 0.1 mm was sliced into 2 cm × 1 cm samples; then ultrasonically cleaned in ethanol and water for 10 min respectively; after cleaning, an oxidation treatment of 30 V was applied for 10 min with graphite as the cathode, and the titanium sheet was electrochemically anodized using an ethylene glycol-based electrolyte with ammonium fluoride (1.2 wt%, 8.18 mM) and water (2 wt%) added; finally, the sample was heat treated at 400 ° C for 3 h to obtain a Ti / TiO2 substrate;
[0100] b. Dendritic silver particle assembly:
[0101] In an ethylene glycol-based electrolytic solution containing 2 mM silver nitrate (AgNO3), with a graphite plate as an anode and Ti / TiO2 as a cathode, dendritic silver particles (Ag ND) were deposited on the surface of Ti / TiO2 at an applied potential of 5 V for 30 s to obtain Ag ND / Ti / TiO2;
[0102] c. Preparation of ZnO quantum dots coated with SiO2 barrier film:
[0103] 20 mL of 0.4 mol / L LiOH·H2O was added to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, and the mixture was stirred at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution. Then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to settle for 2 h. Subsequently, the mixture was centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol. Finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of the ZnO quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@ZnO.
[0104] d. Molecularly imprinted membrane modified SiO 2 @ZnO:
[0105] 50 mg NOR and 500 μL acrylic acid were added to 15 mL methanol solution and stirred for 30 min. Then, 100 mg SiO2@ZnO and 100 μL ethylene glycol dimethacrylate were added and ultrasonically dispersed for 30 min. Then, 20 mg AIBN was added and polymerization was initiated under 360 nm ultraviolet light. Subsequently, the product was collected by centrifugation and washed with methanol. Finally, the obtained polymer was repeatedly eluted with a mixed solution of hydrochloric acid and methanol (1:9, v:v) to remove NOR molecules, forming a molecular imprinted film (MIP) on the surface of SiO2@ZnO, namely, MIP@SiO2@ZnO.
[0106] e.MIP@SiO2@ZnO modification of Ag ND / Ti / TiO2:
[0107] MIP@SiO2@ZnO was dropped onto the surface of Ag ND / Ti / TiO2 to obtain a fluorescence enhanced substrate (MIP@SiO2@ZnO / Ag ND / Ti / TiO2) for targeted detection of norfloxacin, and its detection limit for NOR was 0.019 μmol / L.
[0108] Example 8
[0109] a. Preparation of anodized aluminum substrate:
[0110] 99.7% pure polished aluminum was used as an anodic oxidation material and an electrolytic container with a graphite cathode and temperature regulation. The electrolyte was prepared by mixing phosphoric acid (1.15 mM) and oxalic acid (0.15 mM) at 5°C. A two-electrode system was used with a voltage of 160 V for 40 min to form a nano-columnar oxide layer, which was then immersed in phosphoric acid to enlarge its pores to form an anodic aluminum oxide substrate (AAO);
[0111] b. Dendritic silver particle assembly:
[0112] The prepared AAO substrate was used as cathode, Ag foil as anode, and a mixed solution of 0.01 M AgNO3 and 0.2 M citric acid as electrolyte to electrodeposit dendritic silver particles (Ag ND) on AAO at a current density of 2 mA / cm 2 , work continuously for 300s to obtain AgND / AAO;
[0113] c. Preparation of MoS2 quantum dots coated with SiO2 barrier film:
[0114] 0.08 g / mL Na2MoO4.2H2O and 0.1 g / mL cysteamine hydrochloride were mixed evenly in a volume ratio of 1:2, and the pH was adjusted to 6 with 0.15 mol / L HCl solution; then, the mixture was placed in a reactor at 200°C for 36 h, and the upper layer of light yellow MoS2 quantum dot clear solution was taken for use; subsequently, 60 mL of MoS2 quantum dot solution was added to 120 mL of n-hexane, and a white granular precipitate appeared, which was allowed to settle for 2 h; finally, the mixture was centrifuged for 10 min (2000 r / min), the upper layer of clear solution was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent MoS2 sol; finally, 300 μL of tetraethyl orthosilicate (TEOS) and 100 μL of ammonia water were added to hydrolyze TEOS on the surface of MoS2 quantum dots to form a SiO2 barrier film, thereby obtaining SiO2@MoS2;
[0115] d. Molecularly imprinted membrane modified SiO2@MoS2:
[0116] 50 mg NOR and 500 μL acrylic acid were added to 15 mL methanol solution and stirred for 30 min. Then, 100 mg SiO2@MoS2 and 100 μL ethylene glycol dimethacrylate were added and ultrasonically dispersed for 30 min. Then, 20 mg AIBN was added and polymerization was initiated under 360 nm ultraviolet light. Subsequently, the product was collected by centrifugation and washed with methanol. Finally, the obtained polymer was repeatedly eluted with a mixed solution of hydrochloric acid and methanol (1:9, v:v) to remove NOR molecules, forming a molecular imprinted film (MIP) on the surface of SiO2@MoS2, i.e., MIP@SiO2@MoS2 was obtained.
[0117] e.MIP@SiO2@MoS2 modification of Ag ND / AAO:
[0118] MIP@SiO2@MoS2 was dropped onto the surface of Ag ND / AAO to obtain a fluorescence enhanced substrate (MIP@SiO2@MoS2 / Ag ND / AAO) for targeted detection of norfloxacin, and its detection limit for NOR was 0.041 μmol / L.
[0119] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A fluorescence enhancement substrate for targeted detection of norfloxacin, characterized in that: include: substrate; Noble metal particles located on the surface of the substrate; A fluorescence detection layer located on the surface of the noble metal particles; Wherein, the substrate and the noble metal particles have fluorescence enhancement effect.
2. A fluorescence enhanced substrate for targeted detection of norfloxacin according to claim 1, characterized in that: The substrate is one or more of single crystal silicon, polycrystalline silicon, quartz, glass, fluorine-doped tin dioxide conductive glass, indium tin oxide conductive glass, carbon cloth, paper, cellulose film, stainless steel, metal nickel, metal copper, metal titanium, titanium oxide, metal aluminum, aluminum oxide, indium phosphide, silicon carbide, silicon nitride, diamond, sapphire, gallium arsenide, polydimethylsiloxane, polyethylene terephthalate, polymethyl methacrylate, polyethylene, and polyvinylidene fluoride.
3. A fluorescence enhanced substrate for targeted detection of norfloxacin according to claim 1, characterized in that: The substrate surface has an anti-reflection structure, and the anti-reflection structure is one or more of a pyramid shape, a column shape, a rod shape, a tube shape, a nanowire shape, an inverted pyramid shape, a nanosheet shape, a bowl shape, and a porous shape.
4. A fluorescence enhancement substrate for targeted detection of norfloxacin according to claim 1, characterized in that: The precious metal particles are one or more of silver, gold, copper, platinum and alloys thereof.
5. A fluorescence enhanced substrate for targeted detection of norfloxacin according to claim 1, characterized in that: The micro-nano morphology of the precious metal particles has one of the following shapes: bionic tree branch shape, bionic flower shape, and bionic sea urchin shape.
6. A fluorescence enhancement substrate for targeted detection of norfloxacin according to claim 1, characterized in that: The fluorescence detection layer includes: Fluorescent quantum dots; A fluorescence quenching barrier film located on the surface of the fluorescent quantum dots; a molecular imprinted membrane located on the surface of the fluorescence quenching barrier membrane; Wherein, the molecular imprinting membrane contains a cavity complementary to the spatial structure of the norfloxacin molecule.
7. A fluorescence enhancement substrate for targeted detection of norfloxacin according to claim 6, characterized in that: Norfloxacin is used as a template molecule, and an organic substance containing both an amino group and a hydrolyzable group is used as a functional monomer for hydrolysis, and then norfloxacin is eluted to obtain a molecular imprinting membrane in a fluorescence detection layer.
8. A fluorescence enhancement substrate for targeted detection of norfloxacin according to claim 6, characterized in that: The types of fluorescent quantum dots include one or more of ZnO quantum dots, MgO quantum dots, CuO quantum dots, g-C3N4 quantum dots, CdS quantum dots, SnO2 quantum dots, MoS2 quantum dots, zinc sulfide quantum dots, zinc selenide quantum dots, cadmium selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, graphene quantum dots, and carbon quantum dots.
9. A fluorescence enhancement substrate for targeted detection of norfloxacin according to claim 6, characterized in that: The material of the fluorescence quenching barrier film includes one or more of alumina, SiO2, glass, zirconium oxide, hydroxyapatite, aluminosilicate, and a polymer containing a hydrophilic group.
10. The method for preparing a fluorescence enhanced substrate for targeted detection of norfloxacin according to claim 1, characterized in that: include: Constructing the substrate; assembling noble metal particles onto a substrate surface; Assembling a fluorescent detection layer onto the surface of the noble metal particles; Among them, the assembly technology of precious metal particles includes one or more of chemical deposition technology, electrodeposition technology, electrical displacement reaction technology, and photoreduction technology.